Pacific [large type] : silicon chips and surfboards, coral reefs and atom bombs, brutal dictators, fading empires, and the coming collision of the world's superpowers - Winchester, Simon (HarperLuxe, an imprint of HarperCollinsPublishers, 2015)
The New York Times best-selling author of The Men Who United the States traces the geological history of the Pacific Ocean to assess its relationship with humans and indelible role in the modern world.